A comprehensive study on the processing of Co:ZnO nanostructured ceramics: Defect chemistry engineering and grain growth kinetics. (1st March 2023) - da Silva, R.T.; Morbec, J.M.; Rahman, G.; de Carvalho, H.B.
Highlights: A structural characterization delivered the Co apparent incorporation activation energy and the grain growth parameters. The Ar atmosphere promotes the ZnO incongruent decomposition, leading to a higher Zn i density and a higher Co solubility. To achieve high grain growth and densities the Co3 O4 demonstrated to be a good additive for the w -ZnO sintering. In Ar the metallic Co precursor, due to its higher solubility into the ZnO, leads to a high Co homogeneous distribution over the ZnO grain. CoO present the lowest solubility and final grain size, being the best choice for top-down Co:ZnO nanopowders processing. Abstract: In this report, we present a systematic study on the preparation of Co:ZnO ceramics via a standard solid-state route from different Co precursors (Co3 O4, CoO, and metallic Co) and atmospheres (O2 and Ar). Particular emphasis is given to defect chemistry engineering and the sintering growth kinetics. First-principles calculations based on density functional theory are employed to determine the formation energy of the main point defects in ZnO and Co:ZnO systems. Based on the theoretical results, a set of chemical reactions is proposed. Detailed microstructural characterization is also performed to determine the degree of Co incorporation into the ZnO lattice. The samples prepared in Ar atmosphere and metallic Co present the highest Co solubility limit (lower apparent Co incorporation activation energy) due to the incongruent ZnO decomposition. Determination of the parameters of the sintering growth kinetics reveals that Co3 O4 is the best sintering additive to achieve larger grain sizes, and possible higher densities, in both sintering atmospheres, while metallic Co is the best to achieve the smallest grain size with higher Co concentration and homogeneous spatial distribution for a subsequent reduction of dimensionality. The results show that the sintering in O2 effectively promotes zinc vacancies in the ZnO structure, while the sintering in Ar promotes zinc interstitial defects. Our findings contribute to understanding the preparation of Co-doped ZnO ceramics and the sintering growth kinetics, which may improve the state of the art in processing the material at both bulk and nanometric scales.